2021
DOI: 10.3390/pharmaceutics13122130
|View full text |Cite
|
Sign up to set email alerts
|

Low Blue Dose Photodynamic Therapy with Porphyrin-Iron Oxide Nanoparticles Complexes: In Vitro Study on Human Melanoma Cells

Abstract: The purpose of this study was to investigate the effectiveness in photodynamic therapy of iron oxide nanoparticles (γ-Fe2O3 NPs), synthesized by laser pyrolysis technique, functionalized with 5,10,15,20-(Tetra-4-sulfonatophenyl) porphyrin tetraammonium (TPPS) on human cutaneous melanoma cells, after only 1 min blue light exposure. The efficiency of porphyrin loading on the iron oxide nanocarriers was estimated by using absorption and FTIR spectroscopy. The singlet oxygen yield was determined via transient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Predicted toxicity experiments exhibited the compound potential safety, needing further testing. In addition, the low binding energy between pro-caspase-3 and TPPS indicated a possible tendency of TPPS to inactivate caspase [ 120 ].…”
Section: Nanotechnology (Metallic and Related Nps) Are Significant To...mentioning
confidence: 99%
“…Predicted toxicity experiments exhibited the compound potential safety, needing further testing. In addition, the low binding energy between pro-caspase-3 and TPPS indicated a possible tendency of TPPS to inactivate caspase [ 120 ].…”
Section: Nanotechnology (Metallic and Related Nps) Are Significant To...mentioning
confidence: 99%
“…Generation of ROS for γ-Fe2O3 NPs TPPS is higher than in the case of TPPS alone due to the capacity of NPs to transport the photosensitizer intracellular [9].…”
Section: Introductionmentioning
confidence: 95%
“…In a prior study, we concluded that 5,10,15,20-tetrakis(4'-sulfonatophenyl)-porphyrin tetraammonium (TPPS) is an effective photosensitiser [9]. We explored the mechanisms that cause apoptosis in the Mel-Juso melanoma cell line after incubation with TPPSfunctionalized iron oxide nanoparticles (γ-Fe2O3 NPs TPPS) followed by irradiation, and we came to the following conclusions: First, caspase-3 is active, and pro-caspase-3 levels are reduced, implying that apoptosis is being initiated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations